2020
DOI: 10.3390/w12113246
|View full text |Cite
|
Sign up to set email alerts
|

Dissolved Organic Matter Quality and Biofilm Composition Affect Microbial Organic Matter Uptake in Stream Flumes

Abstract: Agriculture delivers significant amounts of dissolved organic matter (DOM) to streams, thereby changing the composition and biodegradability of the aquatic DOM. This study focuses on the interactive effects of DOM quality and biofilm composition on the degradation of DOM in a laboratory flume experiment. Half of the flumes were exposed to light to stimulate algal growth, the other half was shaded. Leachates of deciduous leaves, maize leaves, and cow dung were added to the flumes in a single pulse and changes o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 71 publications
0
7
0
Order By: Relevance
“…Moreover, in agricultural streams, autotrophic assimilation may dominate, and these systems are often assumed to be net-autotrophic during the growing season (however, see Griffiths et al 2013). Still, there are also indications that the dominance of algae in benthic biofilms might stimulate DOC uptake either directly by priming heterotrophic assimilation with labile DOC, or indirectly by providing a better environment for heterotrophic enzymatic reactions (see Weigelhofer et al 2020) pointing to the possibility of positive feedback between autotrophic and heterotrophic assimilation. Hence, an increase in DOC:nutrient ratios may provoke a stronger response in heterotrophic nutrient assimilation in high-light systems, such as many agricultural streams, compared to low-light systems, such as many forested streams.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in agricultural streams, autotrophic assimilation may dominate, and these systems are often assumed to be net-autotrophic during the growing season (however, see Griffiths et al 2013). Still, there are also indications that the dominance of algae in benthic biofilms might stimulate DOC uptake either directly by priming heterotrophic assimilation with labile DOC, or indirectly by providing a better environment for heterotrophic enzymatic reactions (see Weigelhofer et al 2020) pointing to the possibility of positive feedback between autotrophic and heterotrophic assimilation. Hence, an increase in DOC:nutrient ratios may provoke a stronger response in heterotrophic nutrient assimilation in high-light systems, such as many agricultural streams, compared to low-light systems, such as many forested streams.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Kamjunke et al (2015) observed responses to the quantity and quality of dissolved OM only in planktonic stream microbes but not in benthic biofilms. This indicates that sediment-associated biofilms may be more controlled by internal nutrient and carbon cycling than by the external nutrient supply (Brailsford et al, 2019;Graeber et al, 2018;Wagner et al, 2017;Weigelhofer et al, 2020). In contrast, leaf-and detritus-associated biofilms have OC directly available in their immediate surroundings (Cheever et al, 2012) and may thus require additional nutrients from the water column for enhanced growth.…”
Section: Effects Of Leaf Additions On the Nutrient Uptake By Dark-gro...mentioning
confidence: 99%
“…This is commonly corrected with the absorbance-based approach. From an extra absorbance measurement of the same sample (in the photometer), the effects of the absorbance influencing the fluorescence can be calculated and subsequently corrected (29,30). Absorbance scans were performed between 200 and 700 nm at 0.5 nm intervals (5 cm quartz cuvette; Shimadzu UV-1700 UV-VIS Spectrophotometer).…”
Section: Soil and Sediment Sampling And Analysismentioning
confidence: 99%